Biodiversity in Riffles and Pools of the Mardi and the Vijaypur Streams, Pokhara, Nepal: Benthic Macroinvertebrate Communities - Pokharel, Kishor K. (Tribhuvan University Journal, 2013)
Macro invertebrate communities from September 2003 to August 2004were studied in riffles and pools of the Mardi and the Vijayapur streams, Pokhara, Nepal. A total of 47 genera (32 from the riffles and 34 from the pools) belonging to 38 families and 12 orders were recorded. The generic richness was lower (30 genera) in the Vijaypur stream than in the Mardi stream (38 genera). Ephemeropteran, dipterans, and trichopteran were found predominant orders comprising 11, 8 and 8 genera respectively. Heptagenids, baetids and leptophlebids; chironomids, ceratopagonids and tip lids and hydropsychids, psychomyids and polycentropodids were dominant sub-groups/families among ephemeropterans, dipterans and trichopterans respectively. The dominant genera were, Heptagenia, Rhithrogena and Baetis; Tendipes, Culicoids and Simulium;Hydropsyche and Psychomyia; Psephenus and Heterlimnius; Octogomphus and Argia and Planaria among ephemeropterans, dipterans, trichopterans, plecopterans, coleopherans, odonates and tricladids respectively. The tax occurred at both streams and sub-habitats were, Ephemera, Heptagenia, Rhithrogena, Ecdyonurus, Ephemerella, Baetis, Leptophlebia, Caenis; Tendipes, Culicoides, Simulium; Hydropsyche, Psychomyia, Psephenus, Heterlimnius and Planaria. Those occurred only in the Mardi stream (Site 1) were Habrophlebia, Siphlonurus; Glossosoma, Hydroptila, Leptocerus; Nemoura, Protonemura, Octogomphus, Argia and Gyraulus convexiculus, whereas, only in the Vijaypurstream (Site 2) were Centroptylum; Antocha, Psychoda, Tabanus, Agapetus and Ectopria. The lower taxa richness at the site having urban influence reflects perturbation of riverine environment due to urbanization and needs measures to control further deterioration.